1987
DOI: 10.1172/jci113078
|View full text |Cite
|
Sign up to set email alerts
|

High density lipoprotein2. Relationship of the plasma levels of this lipoprotein species to its composition, to the magnitude of postprandial lipemia, and to the activities of lipoprotein lipase and hepatic lipase.

Abstract: Lipoprotein lipase (LPL) activity in postheparin plasma of 38 normolipidemic volunteers was related to the magnitude of postprandial lipemia after a fat meal, to triglyceride content of high density lipoprotein2 (HDL2), to hepatic lipase (HL) activity, and to HDL2 levels. LPL activity correlated indirectly with lipemia, triglyceride content of HDL2, HL activity, and levels of HDL2 but not of HDL3. HL activity correlated directly with lipemia and indirectly with HDL2 levels.Triglyceride content of HDL2 correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
129
0
4

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(142 citation statements)
references
References 37 publications
(31 reference statements)
9
129
0
4
Order By: Relevance
“…Circulating VLDLs are hydrolysed by two lipolytic enzymes, lipoprotein lipase and hepatic lipase. Both a decrease in lipoprotein lipase and an increase in hepatic lipase activity have previously been shown to be associated with the accumulation of pro-atherogenic small dense LDL particles, a lipoprotein composition that is particularly evident in the presence of increased VLDL concentrations [17,18]. Consistent with the above, we found an independent association between RPB4 levels and hepatic lipase activity in patients with type 2 diabetes and in those with CAD.…”
Section: Discussionsupporting
confidence: 89%
“…Circulating VLDLs are hydrolysed by two lipolytic enzymes, lipoprotein lipase and hepatic lipase. Both a decrease in lipoprotein lipase and an increase in hepatic lipase activity have previously been shown to be associated with the accumulation of pro-atherogenic small dense LDL particles, a lipoprotein composition that is particularly evident in the presence of increased VLDL concentrations [17,18]. Consistent with the above, we found an independent association between RPB4 levels and hepatic lipase activity in patients with type 2 diabetes and in those with CAD.…”
Section: Discussionsupporting
confidence: 89%
“…However, this effect could very well be desireable in obesity and type 2 diabetes; in both conditions plasma triglyceride levels are frequently increased accompanied with CETPmediated loss of HDL-cholesterol. 10,11 In both situations, leptin and insulin levels are high reducing PLTP and CETP levels and consequently loss of HDL cholesterol.…”
Section: Leptin and Insulin On Lipid Transfer Proteins S Kaser Et Almentioning
confidence: 99%
“…6,7 CETP catalyzes the transfer of cholesteryl esters (CE) from HDL to apoB-containg lipoproteins in exchange for triglycerides 8,9 resulting in the conversion of larger to smaller particles and low HDL cholesterol levels. 10,11 Thus, both PLTP and CETP stimulate several critical steps of reverse cholesterol transport.…”
Section: Introductionmentioning
confidence: 99%
“…Patsch et al 42 have shown that this is a critical factor in controlling postprandial lipemia. We have previously shown in subjects eating cholesterol an increase in HDI_2 cholesterol (as a proportion of total cholesterol), which we postulated might have prevented a rise in total cholesterol.…”
mentioning
confidence: 99%